ТЕМПОРАЛЛИК КАТЕГОРИЯСИНИНГ ЛИСОНИЙ-ФАЛСАФИЙ ТАДҚИҚИ ХУСУСИДА (Scientific journal of the Fergana State University, 2023)
The present article is about the analysis of the category of temporality from the point of two subjects – philosophy and linguistics. The peculiarities of the analysis of the category of temporality is carried out within the framework of aspects linguistics like traditional, cognitive, synsemantic, communicative linguistics and functional grammar. Main tendencies of analyzing temporality in linguistics are defined in the article. The analysis of this category in the framework of morphemes conception is suggested in this article.